Demographic profile of patients with acute poisoning in the emergency department of a tertiary care center and their outcomes - Sherpa, Mingmar Chhirring; Nakarmi, Rajan Narayan; Nepal, Suresh Prasad; K.C., Samir; Gupta, Sandeep; Bajracharya, Sunny; Pun, Soosita (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Acute poisoning is a major public health issue in Nepal, driving emergency visits, admissions, and deaths mainly from accessible organophosphorus pesticides. Patterns vary by region, with insecticides dominant in developing areas like Nepal, unlike pharmaceuticals in high-income countries. Limited recent prospective data from Nepalese tertiary centers prompted this study to profile demographics, agents, and outcomes.Methods: A prospective observational study was conducted at Bir Hospital Emergency Department, wards, and intensive care units from July to December 2025. The study included 238 patients aged 14 years and above with acute poisoning. A structured pro forma was used to collect data on demographic variables, poisoning agents, timing, and outcomes. Data analysis was performed using SPSS version 16, employing descriptive statistics and chi-square tests, with a significance level set at p